The Journey Is the Destination: An Exploration of the Experience of Pilgrimage - Walsh, Jessica Jean (Auckland University of Technology, 2022)
Historically, a pilgrimage has referred to a journey undertaken to a sacred place for religious or moral reasons, which often resulted in pilgrims experiencing miraculous healing events (Dubisch & Winkleman, 2005; Talbot, 2002). In modern times, the meaning of pilgrimage has shifted and evolved, though it remains capable of affecting pilgrims in remarkable ways, including psychologically. This study attempts to act as a bridge between pilgrimage and psychotherapy; investigating how the experience of pilgrimage affects pilgrims, in the hope that this knowledge may benefit psychotherapists and the communities they serve. This dissertation proceeds through a hermeneutic literature review, weaving the author’s own process—including her experience on pilgrimage, cultural background, and role as a psychotherapist—with literature on the topic of pilgrimage. The study finds that pilgrimage affects pilgrims in three significant ways: it enables them to feel a healthy sense of community with their fellow pilgrims; facilitates a profound inner journey, alongside their outer journey; and fosters a spiritual connection. Based on these findings and the proven health benefits of community, looking inside oneself and spirituality, it is recommended that pilgrimage be prescribed for clients deemed appropriate by their psychotherapist and utilised as a holistic intervention, alongside regular psychotherapy. Strong connections between Māoritanga and pilgrimage were also discovered, especially regarding the centrality of community, spirituality, and being connected to the natural world. Further recommendations are made pertaining to the relevance of pilgrimage for upholding Te Titiri honouring practice.